Practice of Early Childhood Development Curriculum Preparation - Adhikari, Surya Prasad (Interdisciplinary Research in Education, 2019)
This article aimed to explore early childhood development (ECD) curriculum preparation practices. To accomplish the objective, I have collected qualitative information from ECD center through unstructured interview and discussion with the participant. This study revealed that the respondent has just Montessori basic training on pronunciation and curriculum preparation. Curriculum development center is prepares ECDC curriculums as based on the Wheeler curriculum process. However, private ECDCs prepare curriculum themselves in line with the curriculum development center. Private ECDCs have not compulsory to follow the government’s curriculum. Curriculum of Curriculum Development Center focus on children’s all round developments. But there is lack of spiritual development. Facilitators always start to teach/learn through the objects of the environment. Children learn more words from their mother and parents at home. Facilitators teach children by arranging the words from simple to complex. They teach correct pronunciation, structure of words and then concept.